Financing the future of WHO - Gostin, Lawrence O; Klock, Kevin A; Clark, Helen; Diop, Fatimatou Zahra; Jayasuriya, Dayanath; Jemilah, Mahmood *; Waris, Attiya (Elsevier, 2022)
WHO has anchored the global health architecture since its founding in 1948, and it is impossible to imagine another institution filling the void if the international community were to let it atrophy. While also confronting and guiding the response to COVID-19, WHO is engaged in the most consequential reforms since its founding, including negotiating a global pandemic agreement and revising the International Health Regulations. Underpinning all these reforms is the need for robust and sustainable financing.